RANCANG BANGUN WEBSITE ALSKY STORE SEBAGAI MARKETPLACE DIGITAL LAYANAN TOP UP GAME DAN JASA JOKI MENGGUNAKAN METODE AGILE - Faizal Ersa Alfarobi; Tedi Budiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to design and develop the ALSKY STORE website as a digital marketplace for game top-up and boosting services. The system was developed using the Agile method to support iterative development based on user requirements. The website was built using Laravel 12, PHP, and MySQL, and tested using Black Box Testing. The results show that the system simplifies the ordering, payment, and transaction management processes within an integrated platform. Therefore, the ALSKY STORE website improves service efficiency and provides users with a more convenient digital transaction experience.